Anaphylaxis rates following mRNA COVID-19 vaccination in children and adolescents: Analysis of data reported to EudraVigilance. Issue 14 (31st March 2023) - Maltezou, Helena C.; Hatziantoniou, Sophia; Theodoridou, Kalliopi; Vasileiou, Konstantinos; Anastassopoulou, Cleo; Tsakris, Athanasios
Abstract: Aim: The present study aimed to estimate the anaphylaxis rates following mRNA COVID-19 vaccination in children and adolescents in Europe. Methods: We retrieved data on 371 anaphylaxis cases following mRNA COVID-19 vaccination in children ≤ 17 years old notified to EudraVigilance as of October 8, 2022. Overall, 27, 120, 512 doses of BNT162b2 vaccine and 1, 400, 300 doses of mRNA-1273 vaccine have been delivered to children during the study period. Results: The overall mean anaphylaxis rate was 12.81 [95% confidence interval (CI): 11.49–14.12] per 10 6 mRNA vaccine doses [12.14 (95% CI: 6.37–17.91) per 10 6 doses for mRNA-1273 and 12.84 (95% CI: 11.49–14.19) per 10 6 doses for BNT162b2]. Children 12–17 years old accounted for 317 anaphylaxis cases, followed by 48 cases in children 3–11 years old, and 6 cases in children 0–2 years old. Children 10–17 years old had a mean anaphylaxis rate of 13.52 (95% CI: 12.03–15.00) cases per 10 6 mRNA vaccine doses and children 5–9 years old had a mean anaphylaxis rate of 9.51 (95% CI: 6.82–12.20) cases per 10 6 mRNA vaccine doses. There were two fatalities, both in the 12–17 years age group. The fatal anaphylaxis rate was 0.07 cases per 10 6 mRNA vaccine doses. Conclusions: Anaphylaxis is a rare adverse event after receiving an mRNA COVID-19 vaccine in children. Continuous surveillance of serious adverse events is needed to guide vaccination policies as we move towards SARS-CoV-2 endemicity. Larger real-world studies on COVID-19 vaccination in children, using clinical case confirmation, are imperative.